Effect of Plant-Based Quorum Quenching Compounds as a Feed Additive on the Production Performance of Commercial Broiler Chicken - K.R.Gunasekaran; N. Karthikeyan; J. Ramesh (The Indian Veterinary Journal, 2024)
A biological experiment with six treatment groups was conducted to study the effect of supplementation of plant-based Quorum quenching compounds on production performance and cost of production in commercial broilers (n=720) for a period of five-weeks. A total of 720 one-day-old commercial broiler (COBB 430) chicks (male) were placed in 36 deep litter pens. Each treatment group consist of six replicates with 20 birds per replicate which leads to 120 chicks per treatment. Six experimental diets were formulated based on COBB 430 (2022) specifications with or without antibiotic growth promoter(s) and or Gutsy - a proprietary feed additive developed with an objective to replace antibiotic growth promoters (AGPs) in poultry diet. The level of inclusion (mg/kg) of various products (in feed) such as chlortetracycline (CTC), enramycin, probiotic product and Gutsy are 75, 10, 100 and 150, respectively. The six treatment groups were (1) negative control (w/o AGPs, probiotic and Gutsy; T1), (2) positive control (with both AGPs and probiotic; T2), (3) Gutsy (w/o AGPs, probiotic; T3), (4) combination of all the above (both AGPs, probiotic and Gutsy; T4), (5) CTC and Gutsy (T5) and (6) enramycin and Gutsy (T6). Non-significant (P>0.05) differences were observed in body weight, feed intake and feed conversion ratio (FCR) among the treatment groups during the entire period of study. But, there was a significant difference in livability observed among the treatment groups. The group supplemented with combination of both AGPs, probiotic and Gutsy (T4), achieved the highest livability and European Efficiency factor (EEF; 348) and the lowest cost of production (COP) of Rs. 85.27/kg live weight. So, it can be concluded that Gutsy along with CTC and enramycincould be of highly beneficial for improving the overall performance (EEF) and reducing the COP. While utilizing the same as a replacement for AGPs (T3), it could be of beneficial in improving EEF by 23 points (286vs 309) and reducing the COP by two rupees per kg live weight (89.31 vs 87.31) when compared to the negative control (T1). So, it can be concluded that Gutsy can be incorporated in the diet as an alternative to antibiotic growth promoters (AGPs) in commercial broilers.